Pelatihan Digital Marketing pada Kelompok Industri Jamu Madura Berbasis Focus Group Discussion (FGD) di Kabupaten Pamekasan - Biroli, Alfan; Afifuddin, Mohammad; Bawono, Yudho; Bawono , Priyo Sandi; Aisah , Fitri Nayatul (Santri : Journal of Student Engagement, 2025)
The traditional herbal medicine (jamu) industry in Pamekasan, Madura, which has been passed down through generations, faces significant challenges in marketing in the digital era. Most jamu entrepreneurs still rely on conventional marketing methods, such as direct sales and word-of-mouth, which limit their market reach. Therefore, a community service program based on digital marketing training was conducted to help these entrepreneurs utilize digital technology to expand their market. The training employed a Focus Group Discussion (FGD) method and involved six jamu business owners from Pamekasan. The material covered the basics of digital marketing, strategies for using social media platforms like Instagram and Facebook, as well as marketplace optimization for platforms such as Tokopedia and Shopee. The results of the training showed an increase in participants' understanding of the importance of digital marketing in business development. However, there were still challenges, including low digital literacy, limited technological infrastructure, and complex regulatory requirements for product licensing. Overall, this training had a positive impact, helping the entrepreneurs enhance their competitiveness in broader markets. Continued mentoring and regulatory simplification are needed to ensure the success of the digital transformation of the jamu industry in Pamekasan.